Structural integrity of additive manufactured materials and parts - Shamsaei, Nima; Seifi, Mohsen (Selected technical papers, 2020)
"THIS COMPILATION OF Selected Technical Papers, STP1631, Structural Integrity of Additive Manufactured Materials & Parts, contains peer-reviewed papers that were presented at a symposium held October 7-10, 2019, in National Harbor, MD, USA. The symposium was sponsored by ASTM International Additive Manufacturing Center of Excellence and additional ASTM Technical Committees"--